Successive ligand and metal oxidation: redox reactions involving binuclear CuI complexes of chelating guanidine ligands - Emeljanenko, Dimitri; Peters, Anastasia; Wagner, Norbert; Beck, Johannes; Kaifer, Elisabeth; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2010)
New binuclear complexes of three-coordinate CuI have been synthesized with the ligand 1,2,4,5-tetrakis(tetramethylguanidino)benzene (ttmgb). Subsequent oxidation of the ligand unit was achieved by reaction with Br2 or I2. Reaction with Br2 leads to oxidation of both the ligand and the copper ions and formation of a bicationic dinuclear CuII complex. On the other hand, oxidation with I2 leads only to oxidation of the ligand during the first step. A metastable coordination polymer of ladder-type structure results, in which the coordination number of the CuI ions increases to four. Electrical measurements show that this polymer is semiconductive with a band gap of around 1 eV. The electronic structure of the polymer was further studied by X-ray photoelectron spectroscopy (XPS), Raman and Vis/NIR spectroscopy. It decomposes (with oxidation of the copper ions) in an exothermal reaction at temperatures around 230 °C. Oxidation of the copper ions and decomposition of the polymer can also be achieved by reaction of the polymer with phenanthroline.
Gesehen am 13.03.2023
Im Titelzusatz ist "I" bei "CuI" hochgestellt